Dose de‐escalation to adalimumab 40 mg every 3 weeks in patients with Crohn's disease – a nested case–control study. Issue 7 (6th February 2017) - Van Steenbergen, S.; Bian, S.; Vermeire, S.; Van Assche, G.; Gils, A.; Ferrante, M.
Summary : Background: Data on dose de‐escalation in patients with Crohn's disease (CD) are limited. Aim: To evaluate outcomes of dose de‐escalation from adalimumab (ADM) every other week (EOW) to every three weeks (ETW). Methods: We selected patients with CD receiving maintenance therapy with ADM 40 mg ETW with serum levels (SL) available before and after dose de‐escalation. Sex‐ and age‐matched controls continuing ADM 40 mg EOW were identified. Patient reported outcome, C‐reactive protein (CRP) and serum albumin were collected. Results: Out of 898 patients, we identified 40 (11 male, median 37 years) who de‐escalated to ADM 40 mg ETW for ADM‐related adverse events (AE, n = 1), ADM SL >7 μg/mL ( n = 8), or both ( n = 31). Compared to controls, ADM SL dropped significantly within 4 months, without associated clinical or biochemical changes. In 53% of patients, dose de‐escalation was associated with disappearance of AE (8/16 skin manifestation, 3/6 arthralgia, 5/7 frequent infectious episodes). During a median follow‐up of 24 months, 65% of patients maintained clinical response, but 35% needed dose escalation back to ADM 40 mg EOW because of clinical relapse ( n = 8), ADM SL <4 μg/mL ( n = 2), or both ( n = 4). CRP <3.5 mg/L at dose de‐escalation was independently associated with dose escalation‐free survival [odds ratio 6.28 (95% CI 1.83–21.59), P = 0.004]. We could not define a minimal ADM SL to consider or maintain dose de‐escalation. Conclusions: Overall, 65% of patients who de‐escalated to adalimumab 40 mg every 3 weeks remained in clinical remission for a median of 24 months. In 53% of patients, adalimumab‐related adverse events disappeared after dose de‐escalation. Regardless of adalimumab SL, disease remission should be assessed objectively prior to dose de‐escalation. Abstract : Linked Content This article is linked to Imperatore et al paper. To view this article visithttps://doi.org/10.1111/apt.14128 .